Pusat Kebudayaan Batak Toba Di Kabupaten Tobasa Dengan Pendekatan Arsitektur Neo Vernacular - Andre Giovanni Gultom; Gun Faisal; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The Batak Toba clan is one of the tribes existed in North Sumatra. The Batak Toba tribe has many of artistic and cultural potential. Thus there are also plenty potential natural resources, traditionalarchitecture that displays local cultural values and wisdom. In today's modern era, many people are ignorant of the history and culture of the Batak Toba, resulting in attention and enthusiasmdecreasing about the history and culture of Batak Toba. Therefore, this research aims to design a cultural center for the development and preservation of the potential of the Batak Toba culture inorder to improve people's knowledge about culture and the history of Batak Toba. The selection of Tobasa Regency as the cultural center location because it has well potential, strategic location,cultural heritage and includes the development of the Toba Caldera Geopark area. The method used in this design is the Neo-Vernacular Architecture approach by applying the principles anddesign ideas that exist in the Bolon house with the addition of modern elements in it. The concept used is the transformation of Adaptation Culture concept, which expected to be able to unitebetween architecture with nature and Batak Toba culture aspects. The final result is the design of the Batak Toba Cultural Center which presented the local wisdom of Batak Toba, especially the themodernization of Ruma Bolon however remain expressed local identity.Keyword: Architecture Neo Vernacular, Batak Toba, Culture, Culture Center